Faktor-Faktor yang Berhubungan dengan Kepatuhan Berobat Pasien Skizofrenia di Puskesmas Kedaton Bandar Lampung - Rohmat Tugiwan; Hernida Warni; Ari Sukma Nela (Universitas Nurul Jadid, 2026)
Schizophrenia is a chronic mental disorder that requires long-term treatment to prevent relapse and maintain quality of life. However, non-adherence to treatment remains a major challenge, which can lead to worsening clinical conditions, increased rates of relapse and readmission, and decreased overall function. Several psychosocial factors influence treatment adherence in schizophrenia patients, including patient attitudes, motivation, support from healthcare professionals, and family support. This study aims to determine factors associated with treatment adherence in schizophrenia patients at the Kedaton Community Health Center in Bandar Lampung in 2026. This study used a quantitative design with a cross-sectional approach. A total of 83 respondents with schizophrenia were selected using a purposive sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. Univariate analysis was conducted to describe the frequency distribution of respondent characteristics and study variables, while bivariate analysis using the Chi-Square test was used to determine the relationship between variables. The results showed that in terms of psychosocial factors, 61.4% of respondents had a positive attitude, 65.1% had low motivation, 62.7% received high support from health workers, and 57.8% received good family support. The level of fulfillment of the service was assessed as high (36.1%), moderate (33.7%), and low (30.1%). Bivariate analysis showed a significant relationship between attitude, motivation, support from health workers, and family support with medication adherence in schizophrenia patients (p < 0.05). This study is based on the PRECEDE–PROCEED model, which explains that health behavior is influenced by predisposing factors (attitude and motivation) and reinforcing factors (family and health worker support). Strengthening psychosocial support is very important to improve medication adherence in schizophrenia patients.